Eksistensi bahasa Inggris: Sebuah alat komunikasi dalam gempuran era globalisasi - Nazilah, Nishfi Rohmatun (Maliki Interdisciplinary Journal, 2024)
Since the 19th century, English has been the number one and most widely spoken language in every corner of the world. More than 400 million people speak it as their mother tongue. In this regard, English is commonly used in most aspects of life, such as education, business, technology, and global communication. English is also a tool that bridges communication and is essential for expanding relationships from all sides, especially in today’s era of rapid and extensive globalization. Together with the progress of civilization, the use of English is not only in the world of education. Now, its use extends from the level of daily life to the international world. The ability to speak English is increasingly demanded as time goes by. In this era of globalization, where technology is experiencing many advances, English is needed to face every challenge in the survival of an increasingly modern life. In recent years, English proficiency is no longer associated with the upper class or associated with the United States and Britain as it was in the past. Thus, the era of globalization has changed the existence of English as a basic skill needed by everyone, especially the workforce.